Efektivitas Penggunaan Digital Marketing Sebagai Upaya Peningkatan Brand Awareness dan Keputusan Pembelian pada PT. Nusa Surya Ciptadana Finance Malang - Putri, Elok Islamiyah Dirna; Djaelani, Abdul Kodir; Khalikussabir, Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract Digital marketing is a concept that represents technology as a digital media channel both to promote products or services and also with the aim of building digital brands to increase purchasing decisions and brand awareness. Purchasing decisions are actions taken by consumers to purchase goods or services to fulfill their needs or desires, while building brand awareness in consumers' minds is one of the things that is very crucial in running any business, including the financing business, because it will have an impact on consumers to purchase or use the service. This research uses the AISAS concept (action, interest, search, action and share). This research was carried out using a qualitative approach in its approach method with the type of research used by the researcher being a type of research in the form of a phenomenological method which was analyzed descriptively. The resource person in this research is a credit marketing supervisor from PT. NSC Finance Malang. From the various stages of the phenomenon obtained from sources who were examined using a phenomenological approach, it can be concluded that the effectiveness of the use of digital marketing carried out by PT. NSC Finance Malang, which was reviewed with the AISAS concept, has proven to be effective in increasing brand awareness which will also increase consumer purchasing decisions. Keywords: Digital Marketing, Brand Awareness, Purchasing Decisions, Konsep AISAS